Oklahoma's Indian People Images of Yesterday, Today, and Tomorrow - Oklahoma Univ., Norman. American Indian Inst.; Chisholm, Anita; Oklahoma Univ., Norman. American Indian Inst. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
Designed to be combined with the social studies curriculum, this guide promotes awareness of American Indian contributions to Oklahoma's development and cultural heritage. Lessons help students in grades 6 through 9 strengthen powers of critical thinking, practice writing skills, and develop creative expression, while learning about Oklahoma's 34 federally recognized Indian tribes. Following an introduction in section I, section II provides information of a more general nature regarding the origin of the word "Indian," Oklahoma's current Indian population, the U.S. Government's responsibility to and trust relationships with American Indians, and the Indian reservation system. Lessons in section III develop tribally-specific historical information by providing lessons on specific tribes of each geographic region. Oklahoma's Indian people of the past, present, and future are the subject of section IV, and outstanding persons of various tribes are highlighted. Section V focuses on Indian arts, presenting poems, a play, and a science fiction story written by Oklahoma Indians. Section VI deals with contemporary issues facing Oklahoma's Indian people, including tribal language, cultural heritage, land, and progress issues. Section VII is devoted to culture and discusses family, myths, transition, a ceremonial game, a Pawnee burial, uses of mescal cactus, Ponca singers, a Seneca legend, and traditional housing of the Wichita. Each lesson includes concept, presentation, application (activities and personalization), evaluation, and resources. (LH)
Sponsoring Agency: Oklahoma State Dept. of Education, Oklahoma City.
ERIC Note: Maps and illustrations may not reproduce well.
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: American Indian Culture; American Indian History; American Indian Studies; Cultural Education; Federal Indian Relationship; History Instruction; Intermediate Grades; Junior High Schools; Learning Activities; Social Problems; Social Studies; State History; Tribes; Trust Responsibility (Government); Units of Study; Oklahoma; Guides, Classroom -- Teacher